2021
DOI: 10.1002/slct.202103383
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficiency Fluorescent Probe for Mercury Ions Based on (N, S)‐Co‐Doped Carbon Dots

Abstract: This work demonstrates the preparation of (N, S)‐co‐doped fluorescent carbon dots (N, S‐CDs) for mercury ions (Hg2+) detection. This new fluorescent probe based on N, S‐CDs using dopamine hydrochloride (DA) and L‐cysteine (L‐Cys) as raw materials was reported for the first time. The resulting N, S‐CDs exhibited excellent specificity and selectivity towards Hg2+ and could distinguish them from 26 anions and cations, including Cd2+, Pb2+, and Cr2O72−. The sensor demonstrated high‐intensity fluorescence quenching… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 54 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Sequence alignment indicated that phycobiliproteins may be the main source of the peptides. VTY and LGVP had stronger ACE inhibitory effects, which may be related to the presence of aromatic and hydrophobic amino acid residues in sequence (Zhang et al, 2022a). Chen et al (2020c) extracted peptides from A. platensis by enzymatic hydrolysis and ultrafiltration methods.…”
Section: Proteinmentioning
confidence: 99%
“…Sequence alignment indicated that phycobiliproteins may be the main source of the peptides. VTY and LGVP had stronger ACE inhibitory effects, which may be related to the presence of aromatic and hydrophobic amino acid residues in sequence (Zhang et al, 2022a). Chen et al (2020c) extracted peptides from A. platensis by enzymatic hydrolysis and ultrafiltration methods.…”
Section: Proteinmentioning
confidence: 99%